2017
DOI: 10.1002/ejic.201700465
|View full text |Cite
|
Sign up to set email alerts
|

Vinyl‐Functionalized Silsesquioxanes and Germasilsesquioxanes

Abstract: We report herein an efficient procedure for the synthesis of new polyhedral oligomeric silsesquioxane (POSS) derivatives as multifunctional reagents. This study concerns the incompletely condensed silsesquioxanes and germasilsesquioxanes with vinyl‐substituted silyl and germyl functional groups, which allow further modification. Furthermore, our experiments have been extended to the synthesis of a new subclass of completely condensed vinylgermasilsesquioxanes. These hybrid building blocks were obtained selecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 30 publications
(33 reference statements)
0
14
0
Order By: Relevance
“… 27 We have recently focused on open-cage POSSs, but in this work, the substrate scope was limited only to chlorodimethylvinylsilane and chlorodimethylvinylgermane with various kinds of commercially available POSS silanols. 28 Our recent work has been aimed at the synthesis of a library of IC-POSSs with three types of vinyldiorganosilyl groups and their further catalytic functionalization. Recently, Hreczycho’s group has reported the Sc(OTf) 3 , 29 Bi(OTf) 3 , 30 and also Nafion 31 -catalyzed formation of Si–O–Si bonds, which has been successfully used in the functionalization of POSS silanols, and methods were expanded to the introduction of boron 32 and germanium 33 functionalities to silsesquioxanes.…”
Section: Introductionmentioning
confidence: 99%
“… 27 We have recently focused on open-cage POSSs, but in this work, the substrate scope was limited only to chlorodimethylvinylsilane and chlorodimethylvinylgermane with various kinds of commercially available POSS silanols. 28 Our recent work has been aimed at the synthesis of a library of IC-POSSs with three types of vinyldiorganosilyl groups and their further catalytic functionalization. Recently, Hreczycho’s group has reported the Sc(OTf) 3 , 29 Bi(OTf) 3 , 30 and also Nafion 31 -catalyzed formation of Si–O–Si bonds, which has been successfully used in the functionalization of POSS silanols, and methods were expanded to the introduction of boron 32 and germanium 33 functionalities to silsesquioxanes.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8] In this connection, they have been extensively investigated, especially in materialc hemistry. [13][14][15][16][17] Traditionally,c onventional methods using halo-compounds are used to modify their structure, [18][19][20][21][22] however catalytic solutionsa re becoming increasingly investigated. [13][14][15][16][17] Traditionally,c onventional methods using halo-compounds are used to modify their structure, [18][19][20][21][22] however catalytic solutionsa re becoming increasingly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12] Recently,t he synthesis of functionalizeds ilsesquioxanes cages( SQs) containing other heteroatomsa nd functional groupsh as been strongly developed by many scientists. [13][14][15][16][17] Traditionally,c onventional methods using halo-compounds are used to modify their structure, [18][19][20][21][22] however catalytic solutionsa re becoming increasingly investigated. [23][24][25][26][27][28] On the other hand, the boron modification of variousc ompounds, [29][30][31][32][33] polymers, [34,35] and nanoparticles is attractivef or aw ide range of applications.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the germanium-functionalized POSS compounds containing Ge–O–Si bond in their structure may combine the excellent physical, optical, and electrical properties of silsesquioxanes and the enhanced features of germasiloxanes (e.g., higher refractive index, low dielectric constant, and biocompatible properties). , It is also worth noting that organogermanium compounds have recently aroused much interest in various fields (e.g., as semiconductors in electronic industry, nanocomposite materials, pharmaceuticals and others). , It has been reported that germanium-functionalized materials containing the Ge–O–Si moiety may show improved mechanical properties and thermal stability. , Therefore, the germanium-containing POSS derivatives seem to be particularly attractive for further applications and their properties are still being investigated. Despite their great potential, the number of reports regarding germanium-functionalized silsesquioxanes and the methods for their synthesis is still limited. There are even fewer protocols on the functionalization of incompletely condensed silsesquioxanes with organogermanium groups …”
Section: Introductionmentioning
confidence: 99%
“…To the best of our knowledge, the direct formation of Ge–O–Si bond in all reported literature examples of Ge-functionalized POSS derivatives and germasilsesquioxanes has been achieved using conventional stoichiometric methods. Moreover, there has been only one report regarding incompletely condensed silsesquioxanes with organogermanium functionalities . Marciniec and co-workers have recently reported the synthesis of Ge-substituted incompletely condensed silsesquioxanes, however, their procedure does not eliminate the formation of corrosive and reactive byproducts.…”
Section: Introductionmentioning
confidence: 99%